Motivational-Need Aspects of a Person Involved in Terrorist Activities - K.A. Idrisov; I.S. Hazhuev (Экспериментальная психология, 2023)
Despite significant measures taken by society, the problem of terrorism remains relevant to the entire global community due to its totality, cruelty, pronounced psychological impact on people, and its anti-human orientation. In this regard, research aimed at identifying the overt and hidden motives of terrorist actions, psychological and social factors shaping the unique personality traits of terrorists, and in particular, motivational and need-based aspects of personality that underlie terrorist activity, is of special value. However, such studies are complicated by objective specific circumstances that prevent many researchers from conducting comprehensive research on target samples of individuals involved in terrorist activity. The aim of the study is to examine the socio-psychological attitudes in the motivational-need sphere of personality in individuals involved in terrorist activity, as well as to analyze the psychosocial factors contributing to the formation of these personality constructs. Methods: individual personal examination using a clinical-demographic card specifically adapted for the purposes of the study, and also the diagnosis of socio-psychological attitudes of personality in the motivational-need sphere (using O.F. Potemkina's method).Two samples participated in the study. The first sample - experimental, included 32 individuals - persons under investigation for committing terrorist-related crimes; the second sample - control, included 31 individuals who had no legal problems. All examined are men in the age range from 19 to 45 years. The study results indicate that in this category of individuals, socio-psychological attitudes aimed at altruism and freedom dominate, with low values of egoism and money orientation indicators. It was found that individuals involved in terrorist activity have lower indicators of the formation of such motivational attitudes as process orientation, result orientation, work, freedom, and power, compared to ordinary citizens.